Speech Enhancement through Elimination Of Impulsive Disturbance Using Log MMSE Filtering (International Journal of Engineering and Computer Science, 2013)
The project presents an enhancement of the speech signal by removal of impulsive disturbance from noisy speech using log minimum mean square error filtering approach. Impulsive noise has a potential to degrade the performance and reliability of Speech signal. To enhance the speech component from impulsive disturbance we go for emphasis, signal segmentation and log MMSE filtering. In preprocessing of audio signals start with pre-emphasis refers to a system process designed to increase the magnitude of some frequencies with respect to the magnitude of other frequencies. Emphasis refers to a system process designed to increase the magnitude of some frequencies with respect to the magnitude of other frequencies in order to improve the overall signal-to-noise ratio. Then the signal samples are segmented into fixed number of frames and each frame samples are evaluated with hamming window coefficients. Mean-Square Error Log-Spectral Amplitude (MMSE), which minimizes the mean-square error of the log-spectra, is obtained as a weighted geometric mean of the gains associated with the speech signal. The performance of the filtering is measured with signal to noise ratio, Perceptual Evaluation of Speech Quality (PESQ), Correlation